THE EFFECT OF ENTREPRENEURIAL LEADERSHIP ON MSME PERFORMANCE THROUGH ENTREPRENEURIAL ORIENTATION AND TEAM CREATIVITY (A Study on Aluminium Craftsmen in Genuk, Semarang) - Muhammad Fauzil Adhim; Sumiati, Siti (LP2M IBK Nitro, 2025)
This study aims to analyze the effect of entrepreneurial leadership on the performance of MSMEs, with entrepreneurial orientation and team creativity as mediating variables. The research was conducted on aluminum craft MSMEs in Genuk District, Semarang, using a quantitative approach through a survey of 84 respondents. Data analysis techniques include classical assumption tests, path analysis, and the Sobel test using SPSS 25. The results show that entrepreneurial leadership significantly affects MSME performance, both directly and through the mediation of entrepreneurial orientation and team creativity. The implication of this study emphasizes the importance of developing innovation-based leadership and team collaboration in enhancing the sustainable competitiveness of MSMEs. These findings also enrich the literature on entrepreneurial management in the context of small businesses in Indonesia.